Fed-batch high-cell-density fermentation strategies for Pichia pastoris growth and production. (17th February 2019) - Liu, Wan-Cang; Inwood, Sarah; Gong, Ting; Sharma, Ashish; Yu, Li-Yan; Zhu, Ping
Abstract: Pichia pastoris is extensively used to produce various heterologous proteins. Amounts of biopharmaceutical drugs and industrial enzymes have been successfully produced by fed-batch high-cell-density fermentation (HCDF) of this cell factory. High levels of cell mass in defined media can be easily achieved and therefore large quantities of recombinant proteins with enhanced activities and lower costs can be obtained through HCDF technology. A robust HCDF process makes a successful transition to commercial production. Recently, efforts have been made to increase the heterologous protein production and activity by the HCDF of P. pastoris . However, challenges around selecting a suitable HCDF strategy exist. The high-level expression of a specific protein in P. pastoris is still, at least in part, limited by optimizing the methanol feeding strategy. Here, we review the progress in developments and applications of P. pastoris HCDF strategies for enhanced expression of recombinant proteins. We focus on the methanol induction strategies for efficient fed-batch HCDF in bioreactors, mainly focusing on various stat-induction strategies, co-feeding, and the limited induction strategy. These processes control strategies have opened the door for expressing foreign proteins in P. pastoris and are expected to enhance the production of recombinant proteins.